Influence of emotion on selective attention : some implications for psychopathology. - Lau, Hwee Min. (2012)
The paper reviews empirical investigations that examine the relationship between emotion and attention using the emotional Stroop task and dot-probe paradigm across clinical and non-clinical populations. The literature is structured into three main sections, each considering different aspects of emotional processing. Three factors (self-relevance, trait and state interaction and emotionality) that have the ability to disproportionately bias our attention were reviewed in the first section. In the second section, we examined the components of attentional biases. Particularly, we have determined if the biases are governed by facilitated engagement or problems with disengagement. In the final section, we assessed the stage at which bias processing occur, whether it is automatic (i.e. unconscious) or strategic (i.e conscious). Strong support was given for the role of self-relevant stimuli and the interaction between trait and state emotion in contributing to preferential allocation of attention. The emotionality hypothesis is still unresolved but certain methodological features are accountable for the inconsistent results. Finally, we concluded that both engagement and disengagement govern attentional bias and that these biases can reflect either a conscious or unconscious process, or both depending on the disorder in consideration. Based on the results, clinical implications with respect to treatment procedures were suggested.